2007
DOI: 10.1021/jp075782y
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Adsorption Sites for CO2 in Metal Organic Frameworks Materials MIL-53 (Al, Cr) and MIL-47 (V) by Density Functional Theory

Abstract: A comprehensive DFT study of the possible CO2 adsorption geometries in the MIL-53 (Al, Cr) and MIL-47 hybrid organic−inorganic materials has been performed, as a preliminary step to gain a deeper understanding of the CO2 adsorption mechanism in these systems and to help explain the “breathing” effect displayed by the MIL-53 materials. This technique allows us to explore the possible spatial configurations of the CO2 molecules in the MIL-53 systems depending on the size of the pore opening at different loadings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
125
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 34 publications
(77 reference statements)
15
125
0
2
Order By: Relevance
“…An O Carboxyl -C CO2 interaction is also possible, with similar O Carboxyl -C CO2 distances to the O μ2 -C CO2 ones being predicted by the simulations. This observation is consistent with those previously obtained by our DFT calculations (Ramsahye et al 2007b). A typical illustration of this CO 2 arrangement observed at high loading is provided in Fig.…”
Section: Adsorption In the Mil-47 Materialssupporting
confidence: 93%
“…An O Carboxyl -C CO2 interaction is also possible, with similar O Carboxyl -C CO2 distances to the O μ2 -C CO2 ones being predicted by the simulations. This observation is consistent with those previously obtained by our DFT calculations (Ramsahye et al 2007b). A typical illustration of this CO 2 arrangement observed at high loading is provided in Fig.…”
Section: Adsorption In the Mil-47 Materialssupporting
confidence: 93%
“…Several types of MOFs have been proposed for CO 2 capture, including (i) MOFs with open metal sites, [25][26][27][28][29][30][31][32][33][34][35][36][37] (ii) MOFs without open metals sites, [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] (iii) MOFs with narrow pore size via interpenetration 10,56,57 or shortening the size of the ligands, 10,41 and (iv) MOFs decorated with specific functional groups, including (NH 2 , OH, etc.). 23,51,[58][59][60][61][62][63][64] Functionalization of these types of MOFs may be carried out by post-synthetic modification (PSM) on the open metal sites, 47,[65][66]…”
Section: Discussionmentioning
confidence: 99%
“…29 It is worth mentioning that, to date, many works have shown that pure DFT functionals, such as PW91 and PBE, can often give good qualitative results in evaluating noncovalent interactions such as van der Waals (vdW) interactions in molecular complexes and in the solid state. 25,54Ϫ59 For example, Wesolowski et al studied the binding energies and geometries of benzene with O 2 , N 2 , and CO and found that PW91 can give results comparable in accuracy to the high-level MP2/6-31G** method. 43 In addition, the ESP charges were obtained by using the MerzϪKollman scheme (MK).…”
Section: Modeling and Computational Detailsmentioning
confidence: 99%